LIBROS VENENOSOS AYER Y HOY - Barrios Castro, María José (Myrtia, 2003)
This study, framed into literature of rare books, has the purpose of studying how and in what way poisonous books reflect not only the existence of an unwritten culture, based on the experience and transmitted in an oral way, but a different way of culture appears, ensuing from study, whis has committed itself to those topics.A good number of those books have false believes that nowardays nobobody accepts. Nevertheless those believes are in the culture an oral tradition of a lot of countries. This work is developed from three different viewpoints and demonstrates that the most productive concept is that in which the poison is an author's resource in order to develop the plot.